Banyumasan Context-based Modul Improves Mathematical Literacy in Data Content of Junior High School Students - Nada, Yusrina Qotrun; Isnandar; Usodo, Budi (LPPM Undiksha, 2023)
Learning mathematics is a type of learning that is quite difficult. However, learning will be easier for students to understand if the material presented uses the students' daily context. Learning modules will help students to understand learning in depth. This research aims to develop a mathematics module based on the Banyumasan context. This development research was adapted from the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Data collection methods were carried out through questionnaires and mathematical literacy tests. Data were analyzed using descriptive analysis and quantitative analysis. The research results concluded that: validation results show that the Banyumasan context-based module meets the feasibility standards and is included in the very good category. The results of developing the Banyumasan context-based module were declared practical to use, with a practicality score included in the good category. The results of the development of the Banyumasan context-based module were declared effective in use with the result t-obs = 8.2140 with a critical area of t > 2.030, which means that the mathematical literacy of students who used the Banyumasan context. The context-based module was better than the mathematical literacy of students before using the Banyumasan context-based module. Banyumasan context.